Choroidal Vascular Volume, White Matter Hyperintensity, and Their Interaction With Cognitive Function in Aging Adults - Youjie Wang; Ruilin Wang; Hang Wang; Le Cao; Chen Ye; Junfeng Liu; Bo Wu; William Robert Kwapong; Wendan Tao (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Reports have proposed the retinal choroid as a potential biomarker for dementia and cerebral age‐related disorders. However, the clinical use of the choroid as a surrogate marker remains underexplored. This study investigated the associations among choroidal perfusion, white matter hyperintensity (WMH), and cognitive function. Methods WMH severity (volume and shape features) and choroidal characteristics, including choroidal vascular volume, choroidal vascularity index, and choriocapillaris flow density, were automatically quantified in aging adults. Partial Spearman correlation was used to examine the relationship between choroidal and WMH metrics. General linear models were used to examine the associations of choroidal metrics and WMH characteristics with cognitive performance, as well as to explore potential interaction effects, whereas generalized estimating equations were applied to account for within‐subject correlations in eye‐specific data. Results A total of 197 participants were included in the study. Choroidal vascular volume and choroidal vascular index were inversely correlated with total and periventricular WMH volumes. Irregular WMH shape and reduced choroidal vascular volume were both associated with poorer memory performance. A significant interaction was found between choroidal perfusion and periventricular WMH shape on memory, suggesting that the relationship between WMH features and memory function may be more pronounced in individuals with lower choroidal perfusion. Conclusions The severity of WMH and the status of choroidal perfusion may jointly reflect memory performance, suggesting ischemia as a potential shared mechanism. Future research is warranted to assess the clinical usefulness of WMH and choroidal metrics in predicting cognitive decline.